Crystallographic and enzymatic insights into the mechanisms of Mg-ADP inhibition in the A1 complex of the A1AO ATP synthase - Singh, Dhirendra (2018)
F-ATP synthases are described to have mechanisms which regulate the unnecessary depletion of ATP pool during an energy limited state of the cell. Mg-ADP inhibition is one of the regulatory features where Mg-ADP gets entrapped in the catalytic site, preventing the binding of ATP and further inhibiting ATP hydrolysis. Knowledge about the existence and regulation of the related archaeal-type A1AO ATP synthases (A3B3CDE2FG2ac) is limited. We demonstrate MgADP inhibition of the enzymatically active A3B3D- and A3B3DF complexes of Methanosarcina mazei Gö1 A-ATP synthase and reveal the importance of the amino acids P235 and S238 inside the P-loop (GPFGSGKTV) of the catalytic A subunit. Substituting these two residues by the respective P-loop residues alanine and cysteine (GAFGCGKTV) of the related eukaryotic V-ATPase increases significantly the ATPase activity of the enzyme variant and abolishes MgADP inhibition. The atomic structure of the P235A, S238C double mutant of subunit A of the Pyrococcus horikoshii OT3 A-ATP synthase provides details of how these critical residues affect nucleotide-binding and ATP hydrolysis in this molecular engine. The qualitative data are confirmed by quantitative results derived from fluorescence correlation spectroscopy experiments.